The Practical Aspects of Unifying the Reporting Requirements of Public Benefit Organisations - Zieniuk, Paweł (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The amendment to the accounting law of 15 December 2016 implemented new, unified formats of financial statements for public benefit organisations. Those formats will be applied in reports prepared after the 1st of January 2017. The article presents practical aspects of the new regulations’ implementation in a synthetical manner. From the author’s viewpoint, the new report format matches more the character of activities carried out in the third sector. At the same time, it eliminates problems connected with the need to adjust the format of past reports to the requirements of disclosing revenues and costs of unchargeable, chargeable and economic activities. The results of research carried out on organisations operating in Małopolska are also presented. The research shows the scale of the problem of correctly choosing the format for financial reporting.